2016
DOI: 10.1007/s00421-016-3414-y
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-intensity exercise alters markers of alternative activation in circulating monocytes in females: a putative role for PPARγ

Abstract: PurposeMonocytes may be primed towards differentiation into classically activated M1 macrophages or alternatively activated M2 macrophages. M1 macrophages greatly contribute to the inflammation which promotes insulin resistance, whereas M2 macrophages resolve inflammation. We have previously shown that exercise increases M2 marker expression in mixed mononuclear cells, possibly via activation of the nuclear transcription factor PPARγ. However, these effects have not been demonstrated specifically within monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 66 publications
1
55
0
Order By: Relevance
“…[95][96][97] This might be attributed to acute and chronic effects: strain and acute release of pro-inflammatory mediators are associated with SPM release in acute high-intensity exertion, while chronic effects of exercise intervention might be connected to the exercise-mediated shift in macrophage polarization towards the M2-like phenotype. 95,97,98 M2-like macrophages are better suited to perform efferocytosis than the M1-like phenotype and it is during efferocytosis that SPMs are released. 99 Thus, we know that regular exercise is associated with a shift towards the more proresolving macrophage spectrum, as well as higher levels of pro-resolving mediators, but we do not know which exercise parameters (e.g.…”
Section: Immune-metabolism Interactions and Inflammationmentioning
confidence: 99%
“…[95][96][97] This might be attributed to acute and chronic effects: strain and acute release of pro-inflammatory mediators are associated with SPM release in acute high-intensity exertion, while chronic effects of exercise intervention might be connected to the exercise-mediated shift in macrophage polarization towards the M2-like phenotype. 95,97,98 M2-like macrophages are better suited to perform efferocytosis than the M1-like phenotype and it is during efferocytosis that SPMs are released. 99 Thus, we know that regular exercise is associated with a shift towards the more proresolving macrophage spectrum, as well as higher levels of pro-resolving mediators, but we do not know which exercise parameters (e.g.…”
Section: Immune-metabolism Interactions and Inflammationmentioning
confidence: 99%
“…Exercise can be considered an anti‐inflammatory treatment (Ruffino et al ., ). Firstly, exercise decreases body fat and adipocyte hypertrophy.…”
Section: Introductionmentioning
confidence: 97%
“…36 In parallel, Ruffino et al showed that an 8-week walking-intervention program induced M2-biomarker expression in humans. 37 In another study, Kawanishi et al showed that exercise training reduced macrophage clusters in adipose tissue and increased the number of CD8 + T cells in obese mice. 38 It was shown that exercise training in HFD-fed mice also inhibited adipose-tissue inflammation by inhibiting TNFα, TLR4, and the number of F4/80 macrophages.…”
Section: Discussionmentioning
confidence: 98%